I wonder why stars twinkle and other questions about space - Stott, Carole (New York Kingfisher Books, 1997)
Answers questions about space such as, "Are stars star-shaped," "Which is the coldest planet," and "What is a black hole."
Includes index
1
Keywords: Astronomy -- Miscellanea -- Juvenile literature; Space sciences -- Miscellanea -- Juvenile literature; Astronomy -- Miscellanea; Questions and answers; Outer space -- Miscellanea